Characterisation of Puccinia polysora Underw isolates and rust disease on corn in Peninsular Malaysia - Yusup, Iffatul Arifah (2013)
Corn rust disease which is caused by Puccinia polysora Underw. may incur 40% losses in productivity. In Malaysia there has been little information on this obligate parasite. This study was conducted to examine the sizes and morphology of spores of P. polysora in Selangor and Melaka. Secondly, to distinguish differences between species in these variations in disease symptoms, incidence and severity were also observed and recorded from both locations. The results of study revealed no significant difference between isolates recorded from Selangor. Rust disease was found to be absent in Melaka. The variety planted, time of cultivation and difference in environment condition were possible factors for the difference of rust incidence in the two states.